THE CORRELATION BETWEEN DEMAND FACTORS AND HEALTH CARE SERVICE UTILIZATION BY CONTRIBUTION BENEFICIARY PATIENTS - Leli Rachmawati; Isma Faridatus Sholihah (Universitas Airlangga, 2019)
Background: National Health Insurance is the government's effort to increase public access to health care services. As the implementer of the National Health Insurance, the Outpatient Unit of Haji General Hospital, Surabaya has undergone the decrease of contribution beneficiaries’ visits from 2010-2013. This condition indicates a decrease in health care utilization by the low-income community.Aim: This study aims to identify the correlation between health care demands and health care utilization by the contribution beneficiary patients.Method: The study was an observational analytic using a cross-sectional design. A systematic random sampling technique was used to determine the sample of the study. The respondents were 74 contribution beneficiary patients who possessed a district government free care scheme and had ever utilized the health care services at the Outpatient Unit of Haji General Hospital, Surabaya, and at least 13 years old. The data were collected through questionnaires and analyzed with Spearman and Chi-Square tests (α =0.05).Results: Health status, insurance needs, additional costs, gender, ethnicity, education, and income did not have a significant correlation with the health care service utilization by the contribution beneficiary patients at the Outpatient Unit of Haji General Hospital. It was identified that the older the people are, the higher the frequency of health care utilization is. Besides, service time was proven to be the determinants of health care utilization (p = 0.006).Conclusion: The most influential factors in utilizing the health care services by contribution beneficiary patients are service time and age. Based on those factors, the Haji General Hospital requires to improve its services and service timeliness for the elderly contribution beneficiary patients.Keywords: demand, contribution beneficiary patients, utilization.